ANALYSIS OF SMART TOURISM MODEL IN SOUTH TANGERANG CITY - Bambang Widodo; Ary Rahman (Universitas Sahid, 2021)
The tourism industry is one of the largest foreign exchange earners in Indonesia and is able to provide new jobs. Therefore, tourism is one of the most important sectors in Indonesia, including in the South Tangerang City. South Tangerang City has various tourism potentials ranging from natural tourism, educational tourism, historical tourism, to shopping tourism. One strategy that can be implemented to maximize tourism potential in the South Tangerang City and increase tourist visits is to utilize the application of information technology innovation, also known as the Smart Tourism concept. Smart Tourism can significantly change tourist behavior, number of visits, as well as the function and structure of the tourism industry. This research will discuss how the application of smart tourism in South Tangerang City based on three components, namely smart experience, smart business ecosystem, and smart destination, the impacts of smart tourism implementation, factors that influence the implementation of smart tourism, and strategic analysis of smart tourism model using the SWOT method to determine the relationship between external opportunities and internal strengths and between internal weaknesses and external threats. From this strategic analysis, a strategy will be produced that will be applied in the smart tourism model in South Tangerang City.